2014
DOI: 10.2147/ceor.s46930
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of continuous erythropoietin receptor activator in anemia

Abstract: BackgroundErythropoiesis-stimulating agents (ESAs) are the mainstay of anemia therapy. Continuous erythropoietin receptor activator (CERA) is a highly effective, long-acting ESA developed for once-monthly dosing. A multitude of clinical studies has evaluated the safety and efficiency of this treatment option for patients with renal anemia. In times of permanent financial pressure on health care systems, the cost-effectiveness of CERA should be of particular importance for payers and clinicians.ObjectiveTo crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 65 publications
3
15
0
2
Order By: Relevance
“…Also, in Morocco, our study is the first to evaluate ESA at all. As reported recently by Schmid,9 there are few pharmacoeconomic studies evaluating the cost-utility of CERA; in 18 publications included in his analysis, only one study published as an abstract, reported data about the cost and QALY relative to CERA use in Brazilian dialysis patients; 40 using a model of a hypothetical cohort of CHP treated with CERA or epoetin, the analysis showed that epoetin treatment was more cost-effective than CERA treatment. Unfortunately, it was not possible to compare this study with our results since the access was limited to an abstract.…”
Section: Notesmentioning
confidence: 93%
See 2 more Smart Citations
“…Also, in Morocco, our study is the first to evaluate ESA at all. As reported recently by Schmid,9 there are few pharmacoeconomic studies evaluating the cost-utility of CERA; in 18 publications included in his analysis, only one study published as an abstract, reported data about the cost and QALY relative to CERA use in Brazilian dialysis patients; 40 using a model of a hypothetical cohort of CHP treated with CERA or epoetin, the analysis showed that epoetin treatment was more cost-effective than CERA treatment. Unfortunately, it was not possible to compare this study with our results since the access was limited to an abstract.…”
Section: Notesmentioning
confidence: 93%
“…7 Understanding the relative cost-utility of those treatments is of importance to both clinicians and health care reimbursement authorities, as the acquisition costs of all ESAs are relatively high and are among the top drug expenditures of hospitals, health care payers, and providers. [7][8][9][10] Although all of previous health economic studies focused their analysis on short-acting ESA, CERA as the last one to be introduced in clinical practice has not been well studied yet. 1,7,9,11 The purpose of this study was to determine the cost-utility of treating dialysis patients with CERA once monthly or EpoB thrice weekly compared with a strategy of managing anemia without ESAs.…”
Section: Maoujoud Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Аналіз вартості лікування анемії у пацієнтів з ХХН на додіалізномі етапі показав, що лікування пегильованим еритропоетином- на 23,7% дешевше, ніж застосування дарбопоетину [3]. Аналіз вартості лікування анемії за даними електронних баз MEDLINE, PubMed, Embase та міжнародними базами абстрактів продемонстрував достовірні та переконливі докази економічних переваг використання ЕСЗ тривалої дії у хворих на ХХН [32].…”
Section: вступ анемія є клінічно важливою складовою еволюції хронічнunclassified
“…International guidelines recommend treatment of anaemia due to CKD with erythropoiesis‐stimulating agents (ESAs) (Kidney Disease: Improvement Global Outcomes (KDIGO) Anemia Work Group ; McMahon et al ). The introduction of ESAs has largely replaced red cell blood transfusions for treating anaemia in this patient group, leading to reduced risks of iron overload, blood‐borne virus transmission and alloimmunisation (Schmid ).…”
Section: Introductionmentioning
confidence: 99%